Impact of Employee Engagement, Work Environment, Organizational Culture on Organizational Citizenship Behavior Company: Pengaruh Employee Engagement, Lingkungan Kerja dan Budaya Organisasi Terhadap Organizational Citizenship Behavior Perusahaan - Virgareta, Herlyen; Firdaus, Vera (Indonesian Journal of Law and Economics Review, 2022)
This research was conducted to determine its impact Employee Engagement, work environment, organizational culture on organizational citizenship behavior and intervening effect of job satisfaction at PT Tunas Baru Lampung Tbk, Sidoarjo. This type of research in the researcher uses quantitative methods by distributing questionnaires to 142 respondents of production employees PT Tunas Baru Lampung Tbk, Sidoarjo. Using a proportionate stratified random sampling technique, with a data analysis approach using structural Equation Modeling (SEM) method and analysis tool using AMOS version 24.0. The results of hypothesis concluded that the employee Engegement and organizational culture, with organizational citizenship behavior showed significant results. While the work enviroment does not significantly effect the organizational citizenship behavior.